A Universal Mechanochemistry Allows On‐Demand Synthesis of Stable and Processable Liquid Metal Composites. Issue 7 (26th May 2022) - Wu, Die; Liu, Dingyao; Tian, Xinyu; Lei, Chuxin; Chen, Xianchun; Zhang, Shiming; Chen, Feng; Wu, Kai; Fu, Qiang
Abstract: Gallium‐based liquid metal (LM) is regarded as one of the most promising candidates for the new‐generation jigsaw of stretchable electronics. Nonetheless, the obstacle for the LM application lies in its high surface tension and easy fluidity which leads to great difficulty in handling and processing. Herein, a cross‐mechanochemistry between liquid metal and inorganic solid, mediated via the coordination binding between the empty electronic orbits of the former and the lone electron pair of the latter is reported. The mechanism is validated via density functional theory calculation and electron energy loss spectroscopy, and experimentally proven to be universally applicable for various liquid metals and inorganic solids. With the unique mechanochemistry, simple ball milling allows on‐demand transformation of the liquid metal into a low‐surface‐tension liquid, semi‐solid paste, or even solid powder. The overcoming of the intrinsic high surface tension of the liquid metal with this approach unleashes the freedom to easily process the liquid metal composites into polymer composites or as direct molding processable paste and printable electronic ink. Abstract : A new mechanochemistry between inorganic solids and liquid metals is discovered, mediated via the coordination between the lone electron pair of the former and the empty electronic orbits of the latter. It allows on‐demand transformation of the liquid metal into a low‐surface‐tension liquid, semi‐solid paste, or solid powder, essentially broadening its state‐of‐the‐art applications.